Teacher collaboration in PBL: setting the example for the students - Alves, Anabela Carvalho (2021)
This paper discusses collaboration between teachers in project-based learning (PBL) environments in the engineering context. PBL is a challenging active learning methodology, not only for students but also for teachers. Challenges for teachers include, for example, the need to search for new knowledge demanded by the PBL project theme and the difficulty of aligning their own disciplinary area with interdisciplinary areas in a project. PBL compromises common assumptions of teachers, such as the considerable control over the classroom, reliance on their expert knowledge, predictable programmes to teach, the course assessment, the individual work, among others, whereas, probably, the most challenging aspect of PBL from a teacher perspective is teamwork of the teaching team. Teacher may well feel uncomfortable with sharing knowledge and being exposed and/or assessed by their students and peers. At the same time, PBL requires teachers to think about student achievement and success in first place instead of using more mono-disciplinary course based approach. In this paper, the authors will present evidence through literature review and experience in PBL contexts that such collaboration is highly recommended, if not mandatory, for the PBL success. The paper will also advocate that teacher collaboration is important as an example for students to engage in collaboration.